(untitled) (MAUSAM, 1967)
It is shown that while at Indian electrojet station Annamalainagar some night-time enhancement is seen, at Trivandrum also an electrojet station on the contrary some night-time diminution is seen for all the three phenomena SC, SI and Bay. It is also shown that in Indian zone the mean ratio decreases from north to south while in American zone the mean ratio increases from north to south.